The effect of the use of high doses of ivermectin on liver tissue in rabbits (Journal of Hama University, 2024)
This study aims to find out the macroscopic and histological changes resulting from the administration of high doses of ivermectin in the liver of domestic rabbits, the study was conducted on (32) adult rabbits, the rabbits were divided into four groups and injected under the skin ivermectin and the witness groups injected distilled water, and the groups were given a dose every week for up to four weeks and blood samples were taken for biochemical the results of the biochemical study showed a significant increase (p